The socio-prestational rights as an ideological and structural category - Colque Lizárraga, Alberto (2021)
The purpose of this paper is to address the categories related to social and benefit rights, as well as their guarantees. To this end, it starts from the distinction between first and second-generation rights and finds that their recognition was not due to chronological or structural criteria, but to ideological ones. Thus, the common ideological justification to all social rights is to be found in the egalitarian purpose, which will serve to establish a definitive distinction between ideologically social rights and welfare structural rights. Finally, the topic of primary and secondary guarantees of these rights is developed, pointing out the models that have been proposed for their implementation and the empirical difficulties that have arisen.